2007
DOI: 10.1038/sj.ejcn.1602904
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of dietary carbohydrate quantity and quality in relation to risk of ovulatory infertility

Abstract: Objective: To evaluate whether the amount or quality of carbohydrate in diet is associated with ovulatory infertility. Subjects and Methods: In total, 18 555 married, premenopausal women without a history of infertility were followed as they attempted a pregnancy or became pregnant during an 8-year period. Diet was assessed two times during follow-up using a validated food-frequency questionnaire and prospectively related to the incidence of infertility due ovulatory disorder. Results: During follow-up, 438 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
2
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 53 publications
(50 reference statements)
8
97
2
15
Order By: Relevance
“…With respect to diet, several studies have found associations between a high consumption of low-fat dairy food, animal proteins, trans unsaturated fats, and carbohydrates, as well as high dietary glycemic load, and ovulatory infertility (5)(6)(7)(8). All these findings suggest that insulin and glucose metabolism may affect fertility.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…With respect to diet, several studies have found associations between a high consumption of low-fat dairy food, animal proteins, trans unsaturated fats, and carbohydrates, as well as high dietary glycemic load, and ovulatory infertility (5)(6)(7)(8). All these findings suggest that insulin and glucose metabolism may affect fertility.…”
Section: Introductionmentioning
confidence: 95%
“…From a macronutrient perspective, greater intake of carbohydrates in place of naturally occurring fats was associated with an increased risk of ovulatory infertility in a large cohort of married premenopausal women in the Nurses' Health Study (8). Among the same women, higher protein intake was associated with an increased risk of ovulatory infertility (7).…”
Section: Several Dietary Factors Have Been Associated With the Risk Omentioning
confidence: 99%
“…Diets rich in foods with a high glycaemic index have been associated with an increased risk of diabetes [73], heart disease [74,75], and obesity [76,77], and there are ongoing studies linking diets with a high glycaemic index with age-related macular degeneration [78], ovulatory infertility [79], and colorectal cancer [80]. In this context, energy-restricted diets with a lower glycaemic index can improve energy adaptation during obesity treatment, favouring weight loss and improving lipid (total cholesterol and LDL cholesterol) and glycaemic (insulin and glucose) profiles [81].…”
Section: Diet and Healthmentioning
confidence: 99%
“…Метформин является препаратом первой ли-нии в лечении сахарного диабета 2-го типа, одна-ко обладает и потенциалом в лечении нарушений репродуктивной функции, ассоциированных с ожирением [11]. Действие препарата направлено на повышение чувствительности тканей к инсу-лину и ингибирование глюконеогенеза в печени и широко распространен в лечении именно этой категории пациентов.…”
Section: консервативные способы восстановления репродуктивного здоровьяunclassified
“…Кроме того, выявлено, что ожирение связано с более низкими концент-рациями антимюллерова гормона [11]. У женщин с ожирением наблюдается увеличение концентра-ции С-реактивного белка в фолликулярной жидко-сти, что указывает на то, что метаболическая среда организма имеет прямое воздействие на процессы фолликулогенеза.…”
unclassified